Social Pedagogical Work as Effective Mechanism of Forming Culture of Modern Students - Vydysh, Mykola (Pedagogical Discourse, 2014)
The social pedagogical aspects of problem forming the culture of modern students in establishments of education and indices of culture personality of student are analyzed in the article. It is found out that the culture of modern student youth - it is the method of perception of the world, types of activity, which are folded on the basis of the certain valued orientations, knowledge, persuasions; it is a reflection of qualities inwardly of inherent personality of student; it is a general level of socialization of his personality, which is manifested in progressive activity. The decision of the problem of forming culture of modern student youth depends on how the society and the higher educational establishment as an important social institute, can regulate the practical tendencies of socialization and individualization on every stage of their development. Higher educational establishment becomes the important condition of forming culture of modern student youth, this process must constantly take into account the features of time, adequately to use the different forms of an educational activity and build it on theoretical principles which meet the modern requirements of development of society. Practice shows that one of effective mechanisms of forming culture of modern student youth, is social pedagogical work, which is directed to creation of favorable terms of socialization, comprehensive development of personality, satisfaction of its cultural and spiritual needs.